2022
DOI: 10.3390/diagnostics12051077
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Anti-Endothelial Cell Antibodies (AECAs) in Patients with Polycythemia Vera and Thrombosis

Abstract: Polycythemia vera (PV) causes thrombosis. Erythrocytosis and cell adhesiveness are responsible for thrombosis. JAK2V617F causes inflammation and autoimmunity; however, whether or not autoimmunity or inflammation causes thrombosis has yet to be proven. In 60 PV patients, we analyzed JAK2V671F and its allele burden, autoimmune Th17 cells, interleukin-17 (IL-17), anti-endothelial cell antibodies (AECAs), endothelial leukocyte adhesion molecule-1 (ELAM-1), intercellular adhesion molecule-1 (ICAM-1), and von Willeb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…AECAs were shown to induce apoptosis of the progenitors of bone marrow endothelial cells, which in turn leads to disturbances in endothelial regeneration and the healing of vascular lesions [70]. A number of studies have also indicated that AECAs may exert pathogenic effects by activating endothelial cells to induce a procoagulant phenotype and subsequent thrombosis [69,[71][72][73].…”
Section: Discussionmentioning
confidence: 99%
“…AECAs were shown to induce apoptosis of the progenitors of bone marrow endothelial cells, which in turn leads to disturbances in endothelial regeneration and the healing of vascular lesions [70]. A number of studies have also indicated that AECAs may exert pathogenic effects by activating endothelial cells to induce a procoagulant phenotype and subsequent thrombosis [69,[71][72][73].…”
Section: Discussionmentioning
confidence: 99%
“…AECA were shown to induce apoptosis of progenitors of bone marrow endothelial cells, which leads to disturbances in endothelial regeneration and healing of vascular lesions [57]. Some studies also suggested that AECA may exert pathogenic effects by activating endothelial cells to induce a procoagulant phenotype and subsequent thrombosis [56,[58][59][60].…”
Section: Discussionmentioning
confidence: 99%
“…Others have supported this and have observed that patients receiving HU had lower interleukin IL-6 levels [ 134 , 135 ]. In contradiction, however, others have reported elevated levels of interleukin (IL)-6 compared to untreated patients [ 82 , 106 , 136 , 137 , 138 ].…”
Section: Other Treatment Optionsmentioning
confidence: 99%